1974
DOI: 10.1073/pnas.71.12.5078
|View full text |Cite
|
Sign up to set email alerts
|

A New Antitumoral Agent: 9-Hydroxyellipticine. Possibility of a Rational Design of Anticancerous Drugs in the Series of DNA Intercalating Drugs

Abstract: The designing of DNA intercalating drugs with high DNA affinity in the series of ellipticine has led to a new antitumoral agent, 9-hydroxyellipticine, which has a high DNA affinity, a high activity on L 1210 mice leukemia, and a lack of toxicity at therapeutic dose. The possible correlations among chemical structure, DNA reactivity, and pharmacological activity of DNA intercalating drugs are discussed.Except for the hormonal products, which can prevent specific cells from proliferating, and drugs acting on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
96
0
3

Year Published

1976
1976
2008
2008

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 216 publications
(100 citation statements)
references
References 25 publications
1
96
0
3
Order By: Relevance
“…In the mixed films, both lipids would exist in a very similar and rather condensed state, intermediate between the liquidexpanded and gel states in which these two lipids can respectively exist on pure water. The possibility of membranes being one of the sites of action of ellipticines is discussed.Ellipticine and some of its derivatives constitute an interesting class of substances displaying an antitumoral activity against both experimental and human tumors, as well as other pharmacological propertiesThe mechanism of the cytotoxic action of these drugs is supposedly related to their interactions with DNA for which they exhibit a very high affinity and in which they intercalate [2,3].However, it can be observed in Fig. 1 that ellipticine and its 9-methoxy analogue have a net amphipathic character, a structural feature which endows these substances with the ability to interact with membrane components, especially with phospholipids.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the mixed films, both lipids would exist in a very similar and rather condensed state, intermediate between the liquidexpanded and gel states in which these two lipids can respectively exist on pure water. The possibility of membranes being one of the sites of action of ellipticines is discussed.Ellipticine and some of its derivatives constitute an interesting class of substances displaying an antitumoral activity against both experimental and human tumors, as well as other pharmacological propertiesThe mechanism of the cytotoxic action of these drugs is supposedly related to their interactions with DNA for which they exhibit a very high affinity and in which they intercalate [2,3].However, it can be observed in Fig. 1 that ellipticine and its 9-methoxy analogue have a net amphipathic character, a structural feature which endows these substances with the ability to interact with membrane components, especially with phospholipids.…”
mentioning
confidence: 99%
“…The mechanism of the cytotoxic action of these drugs is supposedly related to their interactions with DNA for which they exhibit a very high affinity and in which they intercalate [2,3].…”
mentioning
confidence: 99%
“…This suggests that the magnitude of uncoupling depends on the concentration of the neutral form released in the matrix after accumulation of the protonated form. Based on membrane potential measurements, it appears that the protonable molecules (1, 3-6) induce a depolarization of the mitochondrial inner membrane much more efficiently than the permanent cation ellipticinium does (2). This comparison suggests that the protonable molecules are able to carry more cationic charges into mitochondria than ellipticinium.…”
Section: Both Protonated and Nonprotonated Forms Are Involved In The mentioning
confidence: 99%
“…A large number of ellipticine derivatives have been synthesized (2) to investigate its mode of action. It has been shown that this molecule is able to intercalate between DNA base pairs (3), and some authors have shown a good in vitro correlation between cytotoxicity and induced dichroic spectra of drug-DNA complexes (4).…”
mentioning
confidence: 99%
“…In this series, 9-hydroxyellipticine ( fig. 1) which displays a high affinity for DNA has been thoroughly investigated [6]. This compound is very active against L1210 mice lymphoid leukemia [7].…”
Section: Introductionmentioning
confidence: 99%